PROBITY AND ETHICS IN POLITICIANS PUBLIC HEALTH SECTOR (Cuestiones de Fisioterapia, 2003)
The probity and honesty shown by civil servants has become a topic of general interest. This paper discusses how probity and honesty are seen by the agents involved in the public health sector as an ethic, financial and social issues.Finally, the authors propose some procedures that could be applied at the micro and macro level in Latin America to improve the probity in the health sector.